Richard Whitford’s Werke for Housholders: Humanism, Monasticism and Tudor Household Piety - Wooding, Lucy E.C. (Studies in church history, 2014)
In 1530 Richard Whitford published A Werke for Housholders, for ‘them that have gydyng and governaunce of any company for an order to be kepte bothe in them selfe | and in them that they have in rule and charge’. The work swiftly went through at least seven editions in as many years; Tudor householders clearly found something of value in its advice. Its author was many things: a Bridgettine monk, a humanist, a prolific author of works in the vernacular, and a survivor who went on writing and publishing even after the dissolution of his monastery. He died in 1543. His books provide some important insights into vernacular humanism and late medieval monasticism, and the often unappreciated relationship between the two, which was demonstrated by his reflections on household piety. This essay argues that Whitford’s Werke for Housholders was rooted in his monastic experience, closely linked to Syon’s pastoral role, and that ideas about the early modern ‘godly household’ should perhaps be adjusted in the light of this connection.